Estudo teórico e experimental de coletor adsortivo - Vieira, Herbert Melo (2009)
This paper presents simple and feasible alternatives that will help improve the performance of a refrigeration system by adsorption, which uses solar energy as a heat source to promote the raising of the temperature of the porous bed, thus occurring, the process of desorption, which is the separation of the adsorbent adsorbato. The studies were made in the modification of the geometry of the absorber plate for triangular tube, which caused an increase in the area provided between the plate and the adsorbent, which were analyzed by a computer program that simulates the cycle of a refrigeration system by adsorption . Another study proposed is the removal of a concentric screen, which aims to promote the flow of radial adsorbato during the processes of sorption, the withdrawal of this screen aims to verify whether the change in the flow of adsorbato of radial to the axial an increase in the concentration of adsorbato the porous bed and if the phenomenon occurs throughout the entire adsorptive column, thus enabling a constructive process of collecting tubular simple plan, this phase of work, is shown through experimental results, verifying the concentration and temperature in two adsorptive columns during the adsorption.